The The Determinants of Resilience, Emotion Regulation, and Self-Efficacy on Psychological Well-Being among Middle-Aged Women - Hoh, Li; Kadek Suranata (Department of Guidance and Counseling, FIP, Undiksha, 2025)
Psychological well-being in middle-aged women is an important aspect influenced by various psychological factors, including resilience, emotion regulation, and self-efficacy. This study aims to identify and analyze the contribution of these three variables to the psychological well-being of middle-aged women in Medan City. Using a quantitative ex post facto design, the study involved 107 respondents aged 40-64 years who are members of the Persaudaraan Dharma Wanita community. Data were collected through valid and reliable questionnaires and analyzed using simple and multiple linear regression after meeting the necessary assumptions. The results show that, partially, resilience and self-efficacy have a significant positive effect, while emotion regulation has a marginally significant effect on psychological well-being. Simultaneously, the three variables significantly influence psychological well-being, with an F value of 27.181 (p < 0.001). The coefficient of determination (R²) of 0.442 indicates that 44.2% of the variance in psychological well-being can be explained by these variables, while the remaining 55.8% is influenced by other factors outside the model. These findings highlight the importance of strengthening resilience, managing emotions, and building self-confidence to maintain mental health in middle-aged women. This study provides a foundation for developing targeted psychological interventions to enhance psychological well-being in this population.